Comparison of Activity and Safety of DSPAα1 and Its N-Glycosylation Mutants - Peng, Huakang; Wang, Nan; Wang, Mengqi; Yang, Caifeng; Guo, Wenfang; Li, Gangqiang; Huang, Sumei; Wei, Di; Liu, Dehu (Life (Basel, Switzerland), 2023)
DSPAα1 is a potent rude thrombolytic protein with high medicative value. DSPAα1 has two natural N-glycan sites (N153Q-S154-S155, N398Q-K399-T400) that may lead to immune responses when administered in vivo. We aimed to study the effect of its N-glycosylation sites on DSPAα1 in vitro and in vivo by mutating these N-glycosylation sites. In this experiment, four single mutants and one double mutant were predicted and expressed in Pichia pastoris. When the N398Q-K399-T400 site was mutated, the fibrinolytic activity of the mutant was reduced by 75%. When the N153Q-S154-S155 sites were inactivated as described above, the plasminogen activating activity of its mutant was reduced by 40%, and fibrin selectivity was significantly reduced by 21-fold. The introduction of N-glycosylation on N184-G185-A186T and K368N-S369-S370 also considerably reduced the activity and fibrin selectivity of DSPAα1. The pH tolerance and thermotolerance of all mutants did not change significantly. In vivo experiments also confirmed that N-glycosylation mutations can reduce the safety of DSPAα1, lead to prolonged bleeding time, non-physiological reduction of coagulation factor (α2-AP, PAI) concentration, and increase the risk of irregular bleeding. This study ultimately demonstrated the effect of N-glycosylation mutations on the activity and safety of DSPAα1.